Conjunctivitis in dupilumab clinical trials. (1st September 2019) - Akinlade, B.; Guttman‐Yassky, E.; de Bruin‐Weller, M.; Simpson, E.L.; Blauvelt, A.; Cork, M.J.; Prens, E.; Asbell, P.; Akpek, E.; Corren, J.; Bachert, C.; Hirano, I.; et al.
Summary: Conjunctivitis is a common condition that causes the eye to become red, itchy and oozing. It is common in patients with atopic dermatitis (also called eczema), and in other allergic diseases, including asthma. Apart from allergies, conjunctivitis can also be caused by infections, chemicals, irritants, and other diseases. Dupilumab is a prescription medicine approved in the USA for people 12 years and older with moderate‐to‐severe AD uncontrolled by topical (applied to the skin) prescription medicines or who cannot use topical medicines, for adults in other countries whose AD is uncontrolled with existing therapies, and for people 12 years and older for maintenance treatment of moderate‐to‐severe asthma uncontrolled with their current medicines. Dupilumab blocks activity of specific substances that cause these allergic diseases. In most AD studies, more dupilumab‐treated patients had conjunctivitis than patients on placebo (dummy drug). To investigate this effect, the authors assessed rates, risk factors, severity, and outcomes of conjunctivitis in 11 dupilumab studies in AD, asthma, chronic rhinosinusitis with nasal polyps (CRSwNP), and eosinophilic esophagitis (EoE). In 5 of 6 AD studies, dupilumab‐treated patients were more likely to get conjunctivitis than placebo‐treated patients. No conjunctivitis was confirmed to be caused by infection, and it does not seem to be allergic in nature. Patients who entered these studies with more severe AD or who previously had conjunctivitis were more likely to get conjunctivitis. In asthma and CRSwNP studies, conjunctivitis rates were less frequent for both dupilumab and placebo than in AD studies, and were similar for dupilumab and placebo. In the EoE study, nobody had conjunctivitis. In all studies, conjunctivitis was mostly mild to moderate; most cases recovered during the treatment period. Causes of conjunctivitis in dupilumab‐treated patients require further study.